Whose resilience matters? Addressing issues of scale in supply chain resilience. Issue 3 (4th March 2021) - Novak, David C.; Wu, Zhaohui; Dooley, Kevin J.
Abstract: Many existing studies and models of supply chain resilience conceptualize resilience from the perspective of an equilibrium‐seeking focal firm or industry. The term "supply chain resilience" is often discussed as a dimension of firm resilience, as opposed to a standalone concept. In this context, resilience is defined according to how well a firm or industry can respond to a disruption while maintaining existing structures and processes and then "bounce back" to a pre‐disruption equilibrium or "bounce forward" to a new, presumably better, equilibrium in the shortest amount of time with the least cost. In this paper, we argue that equilibrium‐based conceptualizations of supply chain resilience can be misaligned with the notion of a supply chain as complex adaptive system (CAS) that continually adapts and transforms via autonomous actions of the different actors within the system. We offer suggestions on how practitioners and researchers can advance theory and practice by adopting a CAS or complexity‐based perspective on supply chain resilience. Specifically, we address the importance of scale and the challenges associated with mismatched scales.